Introductory overview: The OpenMI 2.0 standard for integrating numerical models. (December 2019) - Harpham, Q.K.; Hughes, A.; Moore, R.V.
Abstract: The purpose of this paper is to introduce, explain and promote the Open Modelling Interface (OpenMI) version 2.0 standard for coupling environmental numerical models (simulations of environmental processes). It is intended to be accessible to readers of all levels of experience. During recent decades it has been recognised that the environment is made up of a complex set of interconnected processes. Therefore, understanding the environment requires not only understanding of the processes in isolation, but also the interactions between these processes. Traditional methods of simulating such environmental interactions have included passing the outputs of one numerical model into another or creating a single 'super-model' covering a variety of processes. OpenMI provides a standard method which could be applied to independent numerical model components allowing them to exchange data and therefore influence one another. This is achieved without fundamental changes to the core of the components themselves. Highlights: Main principles of the Open Modelling Interface (OpenMI) version 2.0 standard for coupling environmental numerical models. Underlying drivers and context for the design of the standard. Methods of constructing OpenMI components and compositions. Use Case: River channel – floodplain interactions for flash flooding in Genoa. Use Case: Thames integrated model.